2006
DOI: 10.1381/096089206775565249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Fibrin Glue in the Prevention of Anastomotic Leak and Internal Hernia after Laparoscopic Gastric Bypass: Preliminary Results of a Prospective, Randomized Multicenter Trial

Abstract: The preliminary results suggest that Tissucol application has no adverse effects, is not time-consuming, and may be effective in preventing leaks and internal hernias in morbidly obese patients undergoing LRYGBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Interim results of the present study suggested that major complications may be reduced by the use of fibrin sealant [28]. Here we report the final results of the first prospective, multicenter, randomized clinical trial to evaluate the use of biological fibrin sealant in the prevention of major complications following LRYGBP.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Interim results of the present study suggested that major complications may be reduced by the use of fibrin sealant [28]. Here we report the final results of the first prospective, multicenter, randomized clinical trial to evaluate the use of biological fibrin sealant in the prevention of major complications following LRYGBP.…”
Section: Introductionmentioning
confidence: 68%
“…The surgical procedure consisted of the creation, using linear staplers, of an isolated gastric pouch (estimated volume 15-25 mL), and has been described in detail in a previous publication [28]. Three different surgical techniques were used for the gastro-jejunostomy, depending on the surgeon's personal experience: circular stapling using the 25-mm CEEA Plus (US Surgical Corporation, Norwalk, CT, USA) with the stapler's anvil placed transorally (Gagner technique), linear stapling, or using two layers of handsewn sutures.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Even after gaining experience, surgeons should take adequate care during the preoperative evaluation. Silecchia et al [13] reported the usefulness of fibrin glue in a prospective randomized multicenter trial, and Schweitzer et al [14] reported no anastomotic leakage using a two-layer gastrojejunostomy technique. Although their series did not include a large number of patients, they provided useful information about the best candidates for RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Complications in the clinical use of fibrin sealant can arise because of potential viral or prion infection, patient sensitivity to bovine thrombin and rudimental delivery devices, which affect the final outcome. 30,31 To date, investigations into basic mechanisms of tissue sealant attachment at the tissue interface have not been reported.…”
Section: Fibrin Gluesmentioning
confidence: 99%